Workload intensity and rest periods in professional ballet: Connotations for injury - Kozai, A. C.; Twitchett, E.; Morgan, S.; Wyon, M. A. (International Journal of Sports Medicine, 2020)
Fatigue and overwork have been cited as the main cause of injury with the dance profession. Previous research has shown a difference in workload between professional dancers of different rank, but the role of sex has not been examined. The purpose of this study was to determine workload intensity, rest, and sleep profiles of professional ballet dancers. 48 professional ballet dancers (M=25, F=23) took part in an observational design over 7-14 days using triaxial accelerometer devices. Minutes in METS at different intensities, total time asleep and rest breaks were analysed. Significant main effects for rank (p<0.001) and rank by sex (p=0.003) for total PA, working day activity, post work activity and sleep. Sleep ranged between 2.4-9.6 h per night. All participants spent more time between 1.5-3 METS outside of work. Significant amounts of exercise where carried out outside of their work day, therefore when injury is reported per 1000 h dance activity, this extra-curricular activity might need to be included. When looking at potential causes of injury in dance, a global perspective of physical activity is required that includes activity outside of work and sleep patterns, all activities that influence physiological recovery.